Modified-release phosphatidylcholine (LT-02) for ulcerative colitis: two double-blind, randomized, placebo-controlled trials - Dignaß, Axel Uwe; Stremmel, Wolfgang; Horyński, Marek; Poyda, Oleksandr; Armerding, Peter; Fellermann, Klaus; Langhorst, Jost; Kuehbacher, Tanja; Uebel, Peter; Stein, Jürgen; Novacek, Gottfried; Avalueva, Elena; et al. (Clinical gastroenterology and hepatology, 2024)
Background & Aims - The aim of this study was to evaluate the efficacy of LT-02, a novel modified-release phosphatidylcholine (PC) formulation, for induction and maintenance of remission in patients with mild to moderate ulcerative colitis (UC) and inadequate response to mesalamine. - Methods - LT-02 was evaluated in a multicenter double-blind, randomized, placebo-controlled study comprising a 12-week induction trial (PCG-2), followed by a 48-week maintenance trial (PCG-4). In PCG-2, patients were randomized 1:1:1 to treatment with 0.8 g LT-02 4 times daily (QID), 1.6 g LT-02 twice daily (BID), or placebo, respectively. All patients continued to take a standard dose of oral mesalamine (≥2.4 g/day). The primary end point in PCG-2 was deep remission. Patients achieving remission at week 12 were randomly assigned 2:1:1 to 1.6 g LT-02 BID, placebo, or 500 mg mesalamine (3 times daily), respectively, in PCG-4; the primary end point was remission at 48 weeks. - Results - PCG-2 was terminated early for futility after a prespecified interim analysis; 466 patients (of 762 planned) were randomized. There was no statistically significant difference in deep remission at week 12 (placebo, 13.5%; LT-02 BID, 14.2%; LT-02 QID, 9.7%). In PCG-4, 150 patients (of approximately 400 planned) were randomized. There was no statistically significant difference in remission rates at week 48 (LT-02 BID, 49.3%; mesalamine, 50.0%; placebo, 43.2%). LT-02 was safe. - Conclusions - Despite prior evidence of beneficial effects of PC in phase 2 trials, our induction study with LT-02 in patients with mild to moderate UC was terminated prematurely for futility. Signals of efficacy in maintenance therapy require confirmation in an adequately powered maintenance trial. LT-02 was safe and well-tolerated. ClinicalTrials.gov: NCT02280629, NCT02142725.